Criminal Policy Toward the Crime of Defamation in Cyberspace Through the Use of Deepfake AI - Frensh, Wenggedes (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Currently, humanity is experiencing rapid advancements in science and technology. Information and communication technology has undergone significant developments, particularly with the emergence of Artificial Intelligence (AI). This progress has ushered in the digital era, where people interact in cyberspace through social media platforms that utilize AI. While the use of AI in social media brings positive impacts by enhancing interactions in cyberspace, it also presents the potential for cybercrimes, including defamation through AI-based technology known as Deepfake. Several notable cases of defamation using Deepfake AI have occurred, such as the case of Raffaela Spone in the United States, who sent defamatory Deepfake content targeting members of the Victory Vipers cheerleading team; the manipulated video of Ukrainian President Volodymyr Zelenskyy; the Deepfake video of Indian actress Rashmika Mandanna wearing revealing clothing; and cases involving manipulated Deepfake videos of Indonesian public figures such as Prabowo Subianto, Gibran Rakabuming Raka, and Sri Mulyani. In Indonesia, there is still a lack of clear regulation concerning defamation through the use of Deepfake AI and how to address such crimes through criminal policy. This study aims to examine efforts to combat cyber defamation using Deepfake AI by applying both penal and non-penal criminal policy approaches. The research employs a normative juridical method, using secondary data sources and deductive analysis. The findings show that efforts to address the crime of cyber defamation using Deepfake AI can be implemented through penal policy using formulation strategies, and through non-penal policy by eliminating criminogenic factors contributing to cyber defamation with Deepfake AI. Penal policy countermeasures can be pursued under Law No. 11 of 2008 in conjunction with Law No. 19 of 2016, specifically Article 27 paragraph (3). Non-penal approaches involve the use of Deepfake AI detection technologies, protection of digital identities, digital literacy education, and the enhancement of personal data security.